Teatros verdes: o futebol na cidade e a cidade no futebol - Silva, Fabrício Cardoso da (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation analyzes through the images of the buildings of the Olympic Stadium (1954) and José Pinheiro Borda – Beira Rio Stadium (1969) alongside with the newspapers Jornal do Dia e Diário de Notícias how football participated in this construction of the city's image. The photographs used here are the most exposed by both collections of the clubs, as well as, the articles in the newspapers contribute to understand the plot that led to these architectural works. We will approach this theme through the conceptual look of John Bale (2003), English historian and geographer who developed the term sports landscape. This concept seeks to understand the spaces that are found around the stadiums and that are pieces that participate in the sporting moment itself. Thus, we can approach the city of Porto Alegre and its urban transformations, in the 1950s and 1960s, a period of urban growth that would provide the image that the city has nowadays. Between social disputes, urban housing and political power, football stadiums intertwine with the urban dynamics of the city, building their own imaginary and forever changing the face of the city. Integrating with the layout of the city, the passion for football motivated two architectural works of great scope, modifying the spaces of the city, either in the removal of a village in the case of Grêmio or in the alteration of an environmental landscape, as in the case of Internacional. Thus, the city and its imagery are related to the advent of stadiums and provoke a look at the city of football and its green theaters.
Keywords: Cidade; Estádios de futebol; História do futebol; História urbana; Fotografia; Paisagem esportiva; City; Football stadiums; Football history; Urban history; Photography; Sports landscape; ACCNPQ::Ciências Humanas::História